Genetic divergence among maize hybrids and correlations with heterosis and combining ability - doi: 10.4025/actasciagron.v34i1.11979 (Acta Scientiarum. Agronomy, 2011)
Twelve corn hybrids recommended for cropping in the south-central region of the Paraná State and 66 crossings obtained among these hybrids were evaluated for agronomic and morphological traits. These genotypes were evaluated in three experiments performed in Laranjeiras do Sul, Guarapuava and Cantagalo, Paraná State, Brazil. Heterosis and specific combining ability (SCA) were estimated for yield of husked ears. Data from measuring 22 morphological/agronomical traits of the parents were subjected to a multivariate joint analysis of variance and cluster analysis to group the parental hybrids via the neighbor method, using the generalized Mahalanobis distance. Pearson correlation coefficients between heterosis, SCA, D2 and yield of husked ears were obtained. The cross P30F44 x Sprint displayed a high mean and a high heterosis for yield of husked ears, but a moderate estimate of genetic divergence. Estimates of genetic divergence were not effective at predicting the most heterotic crossings, as Pearson correlation coefficients between D2 and heterosis and D2 and CEC were not significant. Positive significant correlations were observed between yield means and CEC and heterosis.